VD_FINDINFO HC / 2014 / 804 vom 15. September 2014 - VD Tribunal cantonal (2014)
DEMANDE ADRESSÉE À L'AUTORITÉ, INTERPRÉTATIONPROCÉDURE, PÉREMPTION | 125 CPC, 3 CPC, 321 CPC (CH), 327 al. 3 let. b CPC (CH), 334 al. 1 CPC (CH)